The association between landscape design elements and human activities in hot humid outdoor urban spaces - case studies in Kuala Lumpur city - Mohyuddin, Amira; Abdul Majid, Noor Hanita; Sapian, Abdul Razak (2004)
Outdoor urban spaces sustain urban living like oases in the urban desert (Winikoff, 2000). They provide spaces where urban human activities take place. In realizing the activities within outdoor urban spaces in a hot humid climate, the design of these spaces; the layout, the character or image, the design elements and etc contribute much of the attractions of human activities into such spaces. Landscape design elements are among the most obvious attributes of a space, making the space attractive, comfortable and habitable. One cannot deny the associations between man and the physical features in a space, be it natural or man-made, in defining the place. The existence of physical features indirectly attracts people into making the outdoor urban spaces into places.